69 THE PRADER-WILLI CLINICAL SUBPHENOTYPE OF FRAGILE X SYNDROME. (1st January 2006) - Nowicki, S. T.; Tassone, F.; Ferranti, J.; Ono, M. Y.; Hagerman, R. J.
Abstract : Purpose: The Prader-Willi syndrome (PWS) subphenotype of FXS demonstrates severe hyperphagia leading to obesity in addition to more severe behavioral problems with a higher rate of autism than what is typically seen in FXS without the PWS subphenotype. Recently, the FMR1 protein (FMRP) was found to bind to additional proteins including CYFIP1 and CYFIP2 in carrying out its role as a transporter and regulator of translation of mRNAs. With the discovery that CYFIP1 is localized to the region critical for PWS at 15q, the possibility of molecular dysfunction in CYFIP1 in this subphenotype has initiated a detailed study of the clinical subphenotype and comparisons to the known phenotype of PWS. We report our clinical experience with 12 new patients with the (PWS) subphenotype of FXS. Methods: All patients were clinically evaluated to exclude the presence of other disorders. The ADOS, ADI-R, and/or SCQ were completed to assess for autism spectrum disorder (ASD). The cognitive and adaptive ability of each patient was determined. The CGG repeat number, FMR1 mRNA level, and the percentage of FMRP were measured. Results: All of the patients demonstrate severe hyperphagia beginning between 2 and 8 years. Fifty-four percent met criteria for autism based on the ADOS and/or ADI-R. There were lowered CYFIP expression levels in a subgroup of our sample. Conclusions: The PWS subphenotype is associated with a higher rate of ASD. There appears to be a dysregulation in the CYFIP gene in most of the patients evaluated. The deficit in CYFIP expression does not appear to be related to the deletion of the region. Further evaluation of the CYFIP levels in this subphenotype may reveal abnormalities in gene regulation. Expression of CYFIP may be an important gene associated with autism and the PWS subphenotype.